Sincronía y contrastividad en la obra lexicográfica de D. Arturo Agüero Chaves (1996) - Sánchez Corrales, Víctor Manuel (Káñina, 2007)
Sincronía y contrastividad en la obra lexicográfica de D. Arturo Agüero Chaves.